Reactive positioning of pathologically migrated tooth following non-surgical periodontal therapy - Neeraj Agrawal; Prasad SV Siddani (Wolters Kluwer Medknow Publications, 2011)
While contemporary periodontics has witnessed the continued emergence of sophisticated techniques to resolve esthetic concerns through various periodontal procedures, frequently the early stages of periodontal diseases are best treated with non-surgical periodontal therapy. This short communication presents a case of reactive positioning of pathologically migrated anterior tooth following non-surgical periodontal therapy.